Validity assessment of the third molar maturity index (I3M) in a Lebanese sample of adolescents and young adults. Issue 4 (4th July 2022) - Moukarzel, M.; Angelakopoulos, N.; De Luca, S.; Velandia Palacio, L.A.; Aquilanti, L.; Coccia, E.; Pigolkin, Y.I.; Cameriere, R.
ABSTRACT: The validity of third molar index (I3  M  = 0.08) for discriminating minors from adults was tested in a sample of 620 panoramic radiographs of Lebanese subjects (293 females and 327 males), aged between 14 and 23 years. The technical error of measurements (TEM), the relative technical error of measurements (rTEM), the coefficient of reliability (R) and the Intraclass Correlation Coefficient (ICC) were calculated for testing intra- and inter-observer agreement. The I3  M values gradually decreased as age (years) increased across all the age groups in both sexes. For females, the sensitivity and specificity of the test were 0.61 (95% CI: 0.53–0.69) and 0.97 (95% CI: 0.93–0.98), respectively. The sensitivity and specificity for males were 0.63 (95% CI: 0.56–0.70) and 0.89 (95% CI: 0.83–0.93), respectively. The accuracy values (number of correct assessments) were 0.79 (95% CI: 0.74–0.83) for females and 0.74 (95% CI: 0.70–0.79) for males. Estimated post-test probabilities were 0.97 (95% CI: 0.91–0.99) for females and 0.90 (95% CI: 0.83–0.94) for males. The I3  M was a useful further indicator for discriminating between adults and minors in this Lebanese sample of adolescents and young adults.